(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
This study aimed to know the effect of some agricultural substrates on the germination and growth of seedlings pinus pinea and pinus brutia to obtain Exceled seedlings in its shoot and root system. Where used three agricultural substrates : a. Altorf (T): b. Nursery soil (S): c. mixture of Altorf and Nursery soil (TS) by (1: 1). and studied the germination (%) and its speed and several quantities indicators of growth and development of the total shoot and root system of the seedlings for a period of three months. The results showed that the Altorf has played its role in the suitability of the studied species both in terms of germination or in terms of continued growth and development, and also significant differences in the soil medium. Altorf Improved The data and indicators measured at the soil medium alone compared to the mixture at the level of physical, chemical and biological characteristics. On the other hand, the results showed that the plants with the lowest growth contained a greater proportion of the nitrogen. This situation is more evident in pineapple pine. The relief phenomenon is that the concentration of the plant is reduced in the plants of good growth due to its distribution in different parts of the plant. هدفت الدراسة لمعرفة تأثير بعض الأوساط الزراعيّة على إنبات بذور ونمو وتطور بادرات الصنوبر الثمري والبروتي للحصول على غراس متميّزة في تطوّر مجموعها الهوائي والجذري. حيث استخدمت ثلاثة أوساط زراعية هي: أ.التورف (T): ب. تربة المشتل (S): جـ. خليط من التورف وتربة المشتل (TS) بنسبة (1:1). ودرست النسبة المئوية للإنبات وسرعته وعدة مؤشرات كميّة خاصة بنمو وتطور المجموع الخضري والجذري للبادرات. أشارت النتائج إلى أنّ وسط التورف قد لعب دوره الواضح في ملاءمته للنوعين المدروسين سواءً من حيث الإنبات أو من حيث استمرار النموّ والتطور, وباختلافات معنويّة واضحة أيضاً على وسط تربة المشتل. وكذلك حسّن التورف المعطيات والمؤشرات المقاسة عند وسط الشاهد لوحده مقارنةً بخليطه وذلك على مستوى الصفات الفيزيائيّة والكيميائيّة والحيويّة. ومن ناحية أخرى فقد أظهرت النتائج احتواء النباتات ذات النموّ الأقلّ على نسبة أكبر من الآزوت ليؤكِّد هذا الوضع الواضح بشكل أكثر لدى الصنوبر البروتي ظاهرة التخفيف التي تقول بانخفاض تركيز العنصر في النباتات ذات النموّ الجيّد نتيجةً لتوزعه بشكل أكثر على مختلف أجزاء النبات.